Cesarean section rates in Italian regions: 1998-2002 (Italian Journal of Public Health, 2005)
Cesarean section (c-section) rates have been increasing in many countries, and too frequently this rise doesnot seem to be justified by clinical grounds. To reduce c-section rates and achieve a proportion of 20% isamong the goals of the Italian National Health Plan. In the following paper we provide an update on thedistribution of rates amongst Italian regions and describe the association between regional hospitalvolumes and c-section rates. The national c-section rate increased from 31% in 1998 to 36% in 2002. Therates varied among regions and ranged from 20% in the Province of Bolzano to 56% in Campania. Asignificant association was observed between the regional hospital volumes for deliveries and c-sectionrates, regions with low hospital volumes performed more c-sections than high volume regions.
Keywords: Cesarean section; Italy; trends